1977
DOI: 10.1128/aem.34.6.740-744.1977
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Staphylococcus aureus during frankfurter processing

Abstract: We studied the thermal resistance of Staphylococcus aureus during frankfurter processing in respect to whether staphylococci are killed by the heating step of the process and whether heat injury interferes with the quantitative estimation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Thermal processing is the most common intervention against S. aureus and MRSA, and inactivation occurs at 71.1 °C (Palumbo and others ). In a recent study on heat treatment, it was found that chilled storage does not increase the heat resistance of S. aureus , but inactivation temperatures were found to be higher than expected at 75 °C (Kennedy and others ).…”
Section: Methicillin‐resistant S Aureusmentioning
confidence: 99%
“…Thermal processing is the most common intervention against S. aureus and MRSA, and inactivation occurs at 71.1 °C (Palumbo and others ). In a recent study on heat treatment, it was found that chilled storage does not increase the heat resistance of S. aureus , but inactivation temperatures were found to be higher than expected at 75 °C (Kennedy and others ).…”
Section: Methicillin‐resistant S Aureusmentioning
confidence: 99%
“…Frankfurters. The results of this study on survival of MRSA during thermal processing do not differ from the results of Heiszler et al (1972) and Palumbo et al (1977) on thermal inactivation of strains of S. aureus. These two studies differed in cook time to the described experiment above however, because they more closely mimicked large scale commercial manufacturing of frankfurters (30min vs. 95min).…”
Section: Discussioncontrasting
confidence: 57%
“…Previous work (9) has shown that the heating step of the frankfurter process can injure S. aureus added to the emulsion. In the present study, we show that the acid produced by lactic acid starter culture bacteria during the fermentation step in dry and semidry sausage processing can lead to injury of S. aureus present in the sausages.…”
Section: Discussionmentioning
confidence: 99%
“…At various time intervals, 50 g was removed aseptically from a sausage and placed in a sterile polyethylene bag, 200 ml of sterile 0.1% peptone (Difco) water was added, and the mixture was blended for 3 min in a Stomacher 400 blender (Cooke Laboratory Products, Alexandria, Va.). The blended sample was used to determine the surviving S. aureus by direct surface plating of the appropriate dilutions on tryptic soy agar (TSA; Difco) and TSA plus 7.0% NaCl (TSAS) (12) and by the MPN method (brain heart infusion broth enrichment followed by plating on Baird-Parker agar) described by Palumbo et al (9). The lower limit of detection for the plating medium was 25 cells per g, and that of the MPN method was 0.3 cell per g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation